4338590.N14157.Cost-efficiency and Loan Loss Provision Decisions: Evidence from Vietnamese Banking System from 2011 to 2018. - Nguyen, Luong Bao Minh (2019)
This study analyzes bank cost-efficiency level and provisioning managerial behaviors in Vietnam on the data of 37 Vietnamese banks from 2011 to 2018. In theory, the determinants of loan loss provisions (LLP) can be explained under four main hypotheses of capital management, income smoothing, business cycle and signalling theory. In our study, instead of just looking at the above hypotheses, we also link our results of cost-efficiency scores into our LLP model to identify the relation between LLP and bank efficiency. In order to reach our research objectives, this study first generates cost-efficiency scores for individual banks in each year using a cost translog function, then examines the determinants of LLP via System General Method of Moments method. Empirical results support capital management, income smoothing behavior and the impact of cost efficiency on loan loss provision however, we find no evidence of business cycle impact and signalling theory.